One-stage closure of large bronchopleural fistula with pedicled latissimus dorsi muscle flap after preemptive antibiotics: A case report. (2020) - Okada, Satoru; Shimomura, Masanori; Tsunezuka, Hiroaki; Ishihara, Shunta; Ishikawa, Narumi; Kameyama, Kenji; Kitaoka, Shuta; Inoue, Masayoshi
Highlights: Bronchopleural fistula (BPF) often needs two-stage closure after fenestration. This case highlights one-stage surgical closure of a large BPF with a muscle flap. Pedicled latissimus dorsi muscle flap would be useful even for 3-cm sized BPF. Preemptive antibiotics minimized local infection in ischemic bronchitis before BPF. Minimum infection with a limited-size space may be a key for one-stage closure. Abstract: Introduction: Bronchopleural fistula (BPF) after lung cancer surgery is a life-threatening complication and often needs two-stage closure after fenestration. Although one-stage closure of BPF is challenging, it would provide shorter treatment time and lower patient physical burden than two-stage closure. However, there have been few reports of one-stage closure of a large BPF. Presentation of case: A 53-year-old man underwent robotic right lower lobectomy with systematic lymph node dissection. Postoperative bronchoscopy revealed an ischemic change in the bronchial stump, which progressed to a large BPF. However, under the preemptive antibiotic treatment without chest drainage, local infection was controlled within a limited pleural space. We successfully performed one-stage closure of a 3-cm sized BPF with pedicled latissimus dorsi (PLD) muscle flap. Discussion: Early diagnosis of ischemic bronchitis and appropriate preceding antibiotic treatment could minimize the local infection around the fistula. To our knowledge, our case represented the largest BPF that was successfully treated by one-stage procedure using preemptive antibiotics and the PLD muscle flap. Conclusion: One-stage closure using the PLD muscle flap may be a treatment option even for a 3-cm sized BPF, wherein infection is controlled and the relevant pleural cavity is limited.